Advancing sexual health education strategies for young African adults in the digital age - Olamijuwon, Emmanuel (My University, 2021)
Background: The use of social media is gaining intense interest in sexual health promotion. Simultaneously, the sexual health interventions that resonate with their audiences’ needs are known to have the most significant benefits such as the widespread dissemination of health information and the possibility of understanding the complexity of sexual health issues from young people’s perspectives. However, young people superficially interact with sexual health information on social media. It is also unclear how young African adults use social media to access sexual health education and the strategies that motivate the effective use of social media in sexual health promotion. Therefore, the question is: How can engagement with sexuality information on social media be increased and why should social media be an attractive platform and complement for sexual health communication? Theoretical Framework and Objectives: This study evaluated social media use among young African adults for sexuality education in three distinct studies. Specifically, study 1 examined how young African adults interacted with peer generated sexual health information on social media and identified the unique properties of sexual health information associated with higher levels of engagement. Study 2 adapted the unified theory of acceptance and use of technology to identify individual-level factors that predict the intention to use and interact with sexual health information on social media. Lastly, study 3 explored the importance of sexual health promotion on platforms like social media that emphasise multidirectional communication. The study also examined how multidirectional engagement on social media can uncover dominant cultural attitudes and stereotypes, especially on sexuality, marriage, and family. Methodology: This was a mixed-methods study that combined data from an online survey with textual data from a peer-led Facebook group that facilitates discussions about sexuality and sexual health. Study 1 involved a content analysis of 3,533 public wall posts shared on the Facebook group between June 1, 2018, and May 31, 2019. The wall posts were coded into distinct categories comprising the topic classification of the messages, message strategy, and tone of communication. Multiple negative binomial regression models were fitted on the data to delineate statistically significant differences in the levels of engagement with sexuality messages on the group based on multiple categories. To achieve the objective of study 2, a structural equation model with multiple endogenous and exogenous variables was fitted on a sample of 1,190 young adults based in Kenya, Nigeria, and South Africa. Lastly, a thematic analysis was applied to a subsample of 100 public wall posts and 3,860 comments related to sexuality and marriage to uncover lay attitudes related to virginity and marital bliss in study 3. Specifically, I sought to find out how virginity loss is interpreted and perceived to be beneficial for a marriage. Key Findings from Objective 1: The findings from study 1 showed the members of the group were more likely to superficially interact with messages on the group through likes/reactions (x̃= 54) than leave a comment (x̃= 10) or share posts (x̃ = 10) on the group. Rich message features like multimedia use, storytelling, and neutral tone predicted high engagement levels with sexuality information. Therefore, messages that included multimedia content like photos or videos were more likely to be liked [IRR: 1.76; CI: 1.61-1.92], commented on [IRR: 1.16; CI: 1.02-1.32], and propagated [IRR: 1.91; CI: 1.68 - 2.16] compared to text-only messages. The use of fear appeals was also significantly associated with few likes [IRR: 0.75; CI: 0.66-0.86] and comments [IRR: 0.81; CI: 0.67 - 0.99] compared to neutral messages. Key Findings from Objective 2: Young people are amenable to sexuality education on social media. More importantly, young people in the study reported that Facebook (42%) was the most preferred platform for sexuality education while other social media platforms like Twitter (3%) and Instagram (1%) were least preferred. Consistent with the unified theory of acceptance and use of technology, individual characteristics such as performance expectancy [β = 0.18; p < 0.05], effort expectancy [β = 0.25; p < 0.05], social influence [β = 0.09; p < 0.05], facilitating conditions [β = 0.33; p < 0.05], and attitude [β = 0.10; p < 0.05] were significantly associated with the intention to access sexuality information on social media. These attributes, except attitudes to social media use, were also significantly associated with the intention to interact with sexual health information on social media. Key Findings from Objective 3: The findings highlighted the complex multidimensional interpretation of virginity loss by members of the Facebook group. Specifically, young adults in the group interpreted virginity loss as a gift that should be given to someone “special” – particularly a marriage partner. In so doing, participants in the group identified multiple perceived cultural benefits accrued to saving sex for marriage. This included being respected and adorned by the husband and his family, greater partner trust, and marital sexual satisfaction. These interpretations of virginity loss also emphasised the sexual double standard in which a woman is expected to be a virgin while a man is not only expected to be a non-virgin but to also take girls’ virginity. Conclusion: Overall, this study's findings highlight the multiple features associated with interaction with sexuality information on social media. These include rich message features (like multimedia use), good messaging strategy (like storytelling), and a neutral tone of communicating sexual health messages. Individual attributes were also significantly associated with greater engagement with sexuality information on social media. Lastly, the analysis emphasises that sexual health promotion on platforms like Facebook can uncover cultural stereotypes that could put women, girls, and families at risk of poor health and wellbeing. Implications of Findings: Overall, this study highlights several important considerations for advancing the sexual and reproductive health of young African adults. More importantly, it highlights that social media can be a viable complement for existing sexual health information dissemination strategies. The analysis also illuminates how social media could be effectively used in sexual health promotion. The study also highlights the importance of sexual health engagement on platforms like social media that emphasise bidirectional communication as this has the potential to uncover cultural stereotypes that are likely to affect population health, including those without internet access. Such an opportunity may help gain insights into deep-rooted stereotypical attitudes and misconceptions. Frontiers for Further Research: Although this study contributes to the literature in meaningful ways, further studies are needed to identify how young people use sexual health information they obtain from social media platforms. Furthermore, since this is the first study to identify individual attributes associated with greater engagement with sexual health information, more studies are needed to replicate this analysis in different contexts and with additional individual attributes to strengthen the evidence base and improve the predictive power of the models
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy to the Faculty of Humanities, Schools of Public Health and Social Sciences, University of the Witwatersrand, 2021